2020
DOI: 10.3389/fmicb.2020.00796
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Environmental Drivers of Plant Microbiomes Across a Permafrost Thaw Gradient

Abstract: Plant-associated microbiomes are structured by environmental conditions and plant associates, both of which are being altered by climate change. The future structure of plant microbiomes will depend on the, largely unknown, relative importance of each. This uncertainty is particularly relevant for arctic peatlands, which are undergoing large shifts in plant communities and soil microbiomes as permafrost thaws, and are potentially appreciable sources of climate change feedbacks due to their soil carbon (C) stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 81 publications
(135 reference statements)
3
17
0
Order By: Relevance
“…Using a redundancy analysis (RDA, Figure 6) we found that 27.6% of variation in the methanogenic community was explained by two variables: thaw stage (ANOVA, P < 0.05) and depth from the water table (ANOVA, P < 0.05). This percentage is in accordance with other studies conducted in permafrost impacted regions using similar methods, where the percentage of explained variation falls between 6% (low) to 43% (high) (Comte et al, 2015;Hough et al, 2020). Next, we used variance partitioning to assess the extent to which thaw stage and depth from the water table (i.e.…”
Section: Microbial Community Structure Along the Permafrost Peatland Thaw Gradientsupporting
confidence: 84%
“…Using a redundancy analysis (RDA, Figure 6) we found that 27.6% of variation in the methanogenic community was explained by two variables: thaw stage (ANOVA, P < 0.05) and depth from the water table (ANOVA, P < 0.05). This percentage is in accordance with other studies conducted in permafrost impacted regions using similar methods, where the percentage of explained variation falls between 6% (low) to 43% (high) (Comte et al, 2015;Hough et al, 2020). Next, we used variance partitioning to assess the extent to which thaw stage and depth from the water table (i.e.…”
Section: Microbial Community Structure Along the Permafrost Peatland Thaw Gradientsupporting
confidence: 84%
“…Second, inconsistent with our hypothesis, sedges had a limited effect on microbial communities. Oxygenation and substrates from sedge roots are important shapers of microbially driven processes in sedge‐dominated minerotrophic fens (Chanton et al, 2008; Rupp et al, 2019), and of diverse microbial communities associated with sedge rhizospheres (Hough et al, 2020). The modest sedge effect in PEATcosm might be due to their relatively low biomass in the ombrotrophic habitat we focused on, which became more variable through the course of the experiment (Potvin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These shifts in activity are associated with increased activity of ABC transporter genes [ 74 ]. (iv) The extremes of temperature that occur as a consequence of climate change have been demonstrated to affect the phyllosphere and rhizosphere microbiomes of several plants [ 36 ]. (v) Low nitrogen and carbon levels, while not typically thought of as abiotic stresses, (nevertheless they may be considered to be nutrient stress) impact the soil microbiome.…”
Section: Microbiomes and Stressmentioning
confidence: 99%